1974
DOI: 10.14430/arctic2862
|View full text |Cite
|
Sign up to set email alerts
|

An Inferred Sex Differential in Copper Metabolism in Ross' Geese (<i>Anser rossii</i>): Biogeochemical and Physiological Considerations

Abstract: ABSTRACT. The geology and the levels of various minerals in the nutrient chain of the ecosystems of the breeding grounds of most populations of wild geese are distinctive. Hence minerals that become incorporated in the keratin of the primary feathers grown on the breeding grounds can be used as biological tracers to determine origins of migrants. Hormones indirectly affect the levels of some minerals in the feather keratin. Estrogen is presumed to account for higher levels of copper found in the primary feathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Copper Approximately twice the concentration of Cu was detected in the livers of male ducks as in the livers of female ducks in all dosed groups (Table 11). Hanson and Jones (1974) found significantly higher concentrations of Cu in the feathers of female Ross' geese (Anser rossii) than in males.…”
Section: Discussionmentioning
confidence: 85%
“…Copper Approximately twice the concentration of Cu was detected in the livers of male ducks as in the livers of female ducks in all dosed groups (Table 11). Hanson and Jones (1974) found significantly higher concentrations of Cu in the feathers of female Ross' geese (Anser rossii) than in males.…”
Section: Discussionmentioning
confidence: 85%
“…Variability between individuals of the same species is much more complex than within‐individuals and can be confounded with the effect of many variables that are intrinsic to the individual, such as age (Szép et al 2009, Mansouri et al 2015, Óvári et al 2018), sex (Hanson and Jones 1974, Bortolotti et al 1990, Óvári et al 2018), or even diet which can vary between habitats (Kelsall and Burton 1979, Bortolotti and Barlow 1988). Several studies have reported high variability in the mercury concentration of individuals for several seabird species (Furness et al 1986, Bond and Diamond 2008), but there is little information available on other elements or taxa.…”
Section: Discussionmentioning
confidence: 99%
“…It seems axiomatic that each set of flight feathers will, to some degree, reflect the chemistry of the particular area in which it was grown. Some preliminary success in identifying the origins of birds by chemical means have been reported ( Hanson andJones 1968: Devine andPetede 1968).…”
Section: Introductionmentioning
confidence: 99%